Development of broad virus resistance in non-transgenic cucumber using CRISPR/Cas9 technology - Chandrasekaran, Jeyabharathy; Brumin, Marina; Wolf, Dalia; Leibman, Diana; Klap, Chen; Pearlsman, Mali; Sherman, Amir; Arazi, Tzahi; Gal-On, Amit (Molecular plant pathology, 2016)
Summary Genome editing in plants has been boosted tremendously by the development of CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats) technology. This powerful tool allows substantial improvement in plant traits in addition to those provided by classical breeding. Here, we demonstrate the development of virus resistance in cucumber (Cucumis sativus L.) using Cas9/subgenomic RNA (sgRNA) technology to disrupt the function of the recessive eIF4E (eukaryotic translation initiation factor 4E) gene. Cas9/sgRNA constructs were targeted to the N′ and C′ termini of the eIF4E gene. Small deletions and single nucleotide polymorphisms (SNPs) were observed in the eIF4E gene targeted sites of transformed T1 generation cucumber plants, but not in putative off‐target sites. Non‐transgenic heterozygous eif4e mutant plants were selected for the production of non‐transgenic homozygous T3 generation plants. Homozygous T3 progeny following Cas9/sgRNA that had been targeted to both eif4e sites exhibited immunity to Cucumber vein yellowing virus (Ipomovirus) infection and resistance to the potyviruses Zucchini yellow mosaic virus and Papaya ring spot mosaic virus‐W. In contrast, heterozygous mutant and non‐mutant plants were highly susceptible to these viruses. For the first time, virus resistance has been developed in cucumber, non‐transgenically, not visibly affecting plant development and without long‐term backcrossing, via a new technology that can be expected to be applicable to a wide range of crop plants.